Intrapartum antibiotic prophylaxis for Streptococcal B colonisation: a cross-sectional study of hospital internal protocols in Switzerland - Sylvie Anne Genier; Gessica Trivelli; Vera Ruth Mitter (Swiss Medical Weekly)
STUDY AIMS: Streptococcus agalacticae is a pathogen associated with maternal and neonatal morbidity and mortality. The current gold standard for preventing neonatal sepsis is the intrapartum antibiotic prophylaxis (IAP) of Streptococcus agalacticae-positive mothers. Antimicrobial resistance is on the rise and increasingly threatens public health. Therefore, the responsible use of antibiotics is critical. Switzerland lacks unified IAP guidelines. IAP management varies by obstetric ward and is based on various national and international guidelines. This study aimed to gain an overview of the variability of existing internal protocols for IAP for Streptococcus agalacticae in Swiss obstetrics wards.